The Relationship between Health-Promoting Behaviors and Resilience in Patients with Chronic Kidney Disease. (21st March 2013) - Ma, Li-Ching; Chang, Hong-Jer; Liu, Yueh-Min; Hsieh, Hsiang-Li; Lo, Lan; Lin, Mei-Yu; Lu, Kuo-Cheng
Abstract : This cross-sectional research study explored differences in health-promoting behavior and resilience among three groups of chronic kidney disease patients (high-risk, early chronic kidney disease; early CKD and pre-end stage renal disease; pre-ESRD) treated at the Nephrology outpatient clinic in northern Taiwan. A total of 150 CKD outpatients were interviewed using structured questionnaires including a CKD Health to Promote Lifestyle Scale, and resilience scale. We found that the pre-ESRD group had lower resilience than either high-risk or early CKD groups. Factors affecting pre-ESRD resilience were gender, occupational status, diabetes and health-promoting behaviors. Factors affecting resilience of the high-risk group included level of education and health-promoting behaviors while factors affecting resilience in the early CKD group involved whether they are employed and health promoting behaviors. A significant positive correlation was found between health promoting behavior and resilience in all study subjects. Multiple regression analysis found that factors which could effectively predict resilience in patients at high-risk for CKD were gender, whether the patient had a job, nutrition, self-actualization, and stress level, accounting for 69.7% of the variance. Therefore, nursing education should focus on health promotion advocacy throughout the life of not only patients but also their families.